Effects of microstructure and phase composition on the electrochemical activation properties of Ti1.8(VFe)CrNi0.2 + xwt.%LaNi5(x=0, 2.5, 4, 5, 6, 10, 20) metal hydride alloys. (11th January 2018) - Cui, Junjie; Liu, Xiangdong; Lü, Kai; Shang, Junxiao
Abstract: Ti-V-based alloys possess the tremendous hydrogen storage capacity, but low electrochemical activity. In order to improve the electrochemical properties of this kind of alloys, a commercial hydrogen storage alloy, LaNi5, with higher electrochemical activity were introduced and re-melted with Ti1.8 (VFe)CrNi0.2 as master alloy. The new metal hydride composite alloys, Ti1.8 (VFe)CrNi0.2 + x wt.% LaNi5 ( x = 0, 2.5, 4, 5, 6, 10, 20), were prepared and their solidification microstructure and electrochemical characteristics were investigated in this work. It was found that the structural features of the composite alloys varied regularly with increase of amount of LaNi5 . Meanwhile, the microstrain and dislocation, respectively, formed in the major phase and minor phase of the composites. The changes of structural features, especially, the microstrain and dislocation, provided more active sites for hydrogen adsorption, and the symbiosis relation between the phases from the master and the new phases from LaNi5 brought about more crystal interfaces as diffusion path for hydrogen atoms. As a result, hydrogen atoms can be diffused easily from the major phase to minor phase. The results indicated that the composite Ti1.8 (VFe)CrNi0.2 + 5 wt% LaNi5 exhibits the best maximum discharge capacity of 360 mAh/g after 9 cycles. It is found that there are parallel zone axes and similar Kikuchi poles in major phases, and TiNi minor phase of the composite with 5 wt%LaNi5 . It is evident that there exists a symbiosis relation between the major phases and TiNi minor phase. Highlights: The activation properties of LaNi5 -doped Ti1.8 (VFe)CrNi0.2 was first investigated. Specific microstructure and synergetic effect are responsible for activation. Specific microstructure on activation is attributed to the microstrain. The existence of synergetic effect is originated from the symbiosis relation. TiNi phase with BCT structure provides the channel for the hydrogen diffusion.